1995
DOI: 10.1182/blood.v86.3.1072.1072
|View full text |Cite
|
Sign up to set email alerts
|

Loss of blast cell procoagulant activity and improvement of hemostatic variables in patients with acute promyelocytic leukemia administered all-trans-retinoic acid

Abstract: All-trans-retinoic acid (ATRA) induces complete remission (CR) in up to 90% of acute promyelocytic leukemia (APL) patients with rapid amelioration of the bleeding syndrome. Previous studies indicate that ATRA treatment in vitro of the APL NB4 cell line can affect their procoagulant activity (PCA). To assess whether ATRA has this effect also in vivo, we prospectively studied the PCA of bone marrow blasts from APL patients on therapy with ATRA alone or associated with chemotherapy. Samples were obtained before, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
91
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 42 publications
9
91
0
1
Order By: Relevance
“…These findings were confirmed in studies of APML cells following administration of ATRA in vivo. Comparison of APML cells before and after treatment with ATRA demonstrated decreased CP and TF levels with an associated decrease in procoagulant activity (Falanga et al, 1995). Similarly, treatment with ATRA has been shown to downregulate annexin A2 expression (Liu et al, 2011).…”
Section: Atramentioning
confidence: 97%
See 1 more Smart Citation
“…These findings were confirmed in studies of APML cells following administration of ATRA in vivo. Comparison of APML cells before and after treatment with ATRA demonstrated decreased CP and TF levels with an associated decrease in procoagulant activity (Falanga et al, 1995). Similarly, treatment with ATRA has been shown to downregulate annexin A2 expression (Liu et al, 2011).…”
Section: Atramentioning
confidence: 97%
“…ATRA induces terminal differentiation of leukaemic promyelocytes and leads to an immediate improvement in bleeding symptoms and almost complete resolution of the associated coagulopathy within 1-2 weeks of treatment (Dombret et al, 1993;Falanga et al, 1995), but the exact mechanisms behind this have not been completely defined. In vitro studies have shown ATRA to interfere with procoagulant and fibrinolytic mechanisms.…”
Section: Atramentioning
confidence: 99%
“…In vitro studies have demonstrated that ATRA‐induced APL cell differentiation causes loss of expression of CP [22] and TF [23, 24]. TF and CP expression is decreased in bone marrow cells of APL patients given ATRA for remission induction and this decrease precedes normalization of lab abnormalities of coagulation [25]. Thus, tumor‐associated PCA plays a direct role in the clotting complications ofAPL.…”
Section: Procoagulant Activity (Pca)mentioning
confidence: 99%
“…The use of more sensitive diagnostic tests proves that there is increased activity of all three pathways in APL. Levels of thrombin‐antithrombin complex (TAT), prothrombin fragment 1 + 2 (F1 + 2), and fibrinopeptide A, which are all indicators of clotting activation are increased [13, 25, 34]. Elevated levels of FDPs and u‐PA, coupled with depressed plasminogen and α‐2‐antiplasmin levels serve as proof of hyper fibrinolysis [13, 44, 45].…”
Section: Laboratory Testsmentioning
confidence: 99%
See 1 more Smart Citation